The Effect of Personal Words Notes on Enhancing Students’ Vocabulary Mastery - Nur Fadila; Geminastiti Sakkir; Hasriani G (Journal of Excellence in English Language Education, 2023)
This exercise aims to find out how personal word notes affect students' vocabulary. This study used a one-group pre- and post-test experimental design with a focus on quality. According to research, students at MTs Babussalam can use Personal Words Notes (PWN) in class, based on the findings and discussion of chapters and findings of papers. The purposive sample that suits the two students is different. Test data (both after and after the test) are collected. The results show that the "Poor" frequency of the pretest mean score is 44.8. The coefficient of "Good" for the post-test mean score is 87.2. Therefore, a comparison of the student's vocabulary with personal notes can be calculated, which shows that the exercise is based on the student's vocabulary.